2018
DOI: 10.1002/jlb.3ab0718-255r
|View full text |Cite
|
Sign up to set email alerts
|

GILZ restrains neutrophil activation by inhibiting the MAPK pathway

Abstract: Glucocorticoid-induced leucine zipper (GILZ) exerts anti-inflammatory effects on the immune cells. However, less is known about GILZ function in neutrophils. We aimed to define the specific role of GILZ in basal neutrophil activity during an inflammatory response. GILZ knockdown resulted in a persistent activation state of neutrophils, as evidenced by increased phagocytosis, killing activity, and oxidative burst in GILZ-knockout (KO) neutrophils. This enhanced response caused severe disease in a dinitrobenzene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…Hence, corticosteroids have proinflammatory effects in neutrophils. Corticosteroids are generally thought to weakly suppress neutrophilic inflammation, although several research groups reported them to inhibit the neutrophil respiratory burst and interfere with neutrophil recruitment ( Strausbaugh and Rosen, 2001 ; Ronchetti et al, 2018 ; Ricci et al, 2019 ). For instance, corticosteroids do not improve neutrophilic inflammation in corticosteroid-resistant asthma or COPD ( Yang et al, 2012 ; Ronchetti et al, 2018 ).…”
Section: Drugs Targeting Neutrophils For Covid-19 Associated Ardsmentioning
confidence: 99%
“…Hence, corticosteroids have proinflammatory effects in neutrophils. Corticosteroids are generally thought to weakly suppress neutrophilic inflammation, although several research groups reported them to inhibit the neutrophil respiratory burst and interfere with neutrophil recruitment ( Strausbaugh and Rosen, 2001 ; Ronchetti et al, 2018 ; Ricci et al, 2019 ). For instance, corticosteroids do not improve neutrophilic inflammation in corticosteroid-resistant asthma or COPD ( Yang et al, 2012 ; Ronchetti et al, 2018 ).…”
Section: Drugs Targeting Neutrophils For Covid-19 Associated Ardsmentioning
confidence: 99%
“…Its interactions with signal transduction pathways, many of which are operative in RA and other inflammatory diseases, suggest that it is a key endogenous regulator of the immune response including a key glucocorticoid-induced regulator of inflammation in rheumatoid arthritis (RA) (Beaulieu and Morand, 2011). GILTZ is a small, 135-amino acid protein with anti-inflammatory properties and has been shown to inhibit NF-ÎșB and MAPK pathways (Bereshchenko et al, 2019;Ricci et al, 2019). It has also been shown to be induced in response to hypoxia by a HIF1α-dependent mechanism and in response to cholesterol starvation, leading to downstream shedding of procoagulant EVs in ovarian cancer (Koizume et al, 2019).…”
mentioning
confidence: 99%
“…Out of these, 256 and 200 genes were successfully annotated in the VEH-untreated/SIV and THC/SIV groups, respectively. At least five genes with well-established functions in maintaining oral epithelial barrier integrity AGR2 [ 58 , 59 ], WFDC2 [ 60 , 61 ], anti-inflammatory function ( TSC22D3 ) [ 62 , 63 , 64 ] and prevention of oxidative stress [ 48 , 65 ] were found to be significantly downregulated in OPM of VEH-untreated/SIV rhesus macaques ( Figure 1 D). On the other hand, proinflammatory extracellular matrix degrading proteinases ( MMP7 ) [ 66 ], endoplasmic reticulum (ER) stress regulating and anti-viral CREB3L1 [ 67 ] and DNA demethylating APOBEC2 [ 68 ] were significantly downregulated in OPM of THC/SIV rhesus macaques ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 99%
“…Further, WFDC2 is expressed by MiSGs [ 60 , 61 ] and in association with other related WAP domain containing proteins functions in epithelial host defense. Finally, the expression of TSC22D3 , also known as glucocorticoid induced leucine zipper ( GILZ ), is stimulated by glucocorticoids and IL10 and is well described to play a key role in mediating the anti-inflammatory and immunosuppressive effects of both proteins [ 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%